E-Service Quality, Islamic Branding, and Islamic Advertising Ethics on Product Purchase Decisions with Celebrity Endorsers as Intervening Variables (Case of UIN Postgraduate Student Shopee Customer) - Fajriany S, Imaniar Nur; Juanda Zulqadri; Siradjuddin (Yayasan Meira Visi Persada, 2025)
This study aims to determine the Influence of E-Service Quality, Islamic Branding, Islamic Advertising Ethics on Product Purchase Decisions with Celebrity Endorsers as an Intervening Variable (Case of UIN Postgraduate Students Shopee Customers). The research method uses a quantitative approach with the research object of UIN Alauddin Makassar Postgraduate Students, with a total of 87 research samples. The SmartPLS method was used to analyze the data, and the study's findings indicate that E-Service Quality, Islamic Branding, and Islamic Advertising Ethics all significantly and favorably influence consumers' decisions to buy. The relationship of indirect influence through celebrity endorsers, the Electronic While the Islamic branding variable demonstrates that the celebrity endorser variable can mediate the purchase decision, and the Islamic advertising ethics variable has a positive and significant impact on the purchase decision through celebrity endorsers, the service quality variable has a positive and significant impact on purchase decisions.